2012
DOI: 10.1111/j.1539-6924.2012.01771.x
|View full text |Cite
|
Sign up to set email alerts
|

Unquestioned Answers or Unanswered Questions: Beliefs About Science Guide Responses to Uncertainty in Climate Change Risk Communication

Abstract: In two experimental studies we investigated the effect of beliefs about the nature and purpose of science (classical vs. Kuhnian models of science) on responses to uncertainty in scientific messages about climate change risk. The results revealed a significant interaction between both measured (Study 1) and manipulated (Study 2) beliefs about science and the level of communicated uncertainty on willingness to act in line with the message. Specifically, messages that communicated high uncertainty were more pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 39 publications
1
84
0
6
Order By: Relevance
“…Psychology undergraduates at least can judge both science and nonscience arguments by the amount and reliability of their evidence (9). Different lay people hold different models of science, some more classical (seeking a single, true answer) versus others more Kuhnian (acknowledging multiple answers to negotiate and debate, accepting scientific uncertainty) (10). Hence, potential divides between scientists and the public are not merely about sheer knowledge in any simple way.…”
Section: Public Beliefs and Affectmentioning
confidence: 99%
“…Psychology undergraduates at least can judge both science and nonscience arguments by the amount and reliability of their evidence (9). Different lay people hold different models of science, some more classical (seeking a single, true answer) versus others more Kuhnian (acknowledging multiple answers to negotiate and debate, accepting scientific uncertainty) (10). Hence, potential divides between scientists and the public are not merely about sheer knowledge in any simple way.…”
Section: Public Beliefs and Affectmentioning
confidence: 99%
“…Does more knowledge inevitability reduce uncertainty and how people approach scientific research and its applications? Rabinovich and Morton (2012) propose that beliefs about the scientific process and levels of uncertainty communicated about scientific phenomenon can affect willingness to act on messages that call for adapting to climate change. They contrast two models of the nature of science that underlie the meanings assigned to uncertainty.…”
Section: Abstract: Adaptive Management-beliefs-climate Change-informmentioning
confidence: 99%
“…People and the institutions they are associated with have different levels of tolerance for uncertainty and different strategies for reducing it when there seems to be a benefit in doing so. In general, people typically look for certainty and avoid uncertainty when deciding how to act in their everyday lives (Slovic 2009;Rabinovich and Morton 2012).A claim of scientific uncertainty is often interpreted by the nonscientific public as a sign of incompetence or poor understanding about a topic (Frewer et al 2003) rather than an admission of incomplete information. There is evidence that people tend to discount information labeled "uncertain" in the process of decision making, and are less likely to use information that conveys uncertainty (Rabinovich and Morton 2012).…”
mentioning
confidence: 99%
“…Changes in climate are generally slow and modifications of average climate conditions gradually occur over long time periods (Weber 2010), which has influenced public receptiveness on addressing the issue of climate change (Leiswerowitz et al 2012). It has been documented that individual beliefs in scientific consensus (Lewandowsky et al 2012), risk perceptions and beliefs (Leiserowitz 2006), and trust in information source (Rabinovich and Morton 2012;Maibach et al 2011;Weber 2010) influence an individuals' willingness to become receptive to climate science information and utilize it in their decision making process. This is also evident in the agricultural sector, where it has been found that trust in information sources influences beliefs, and subsequently behaviors, about climate change (Arbuckle et al 2013a).…”
Section: Resultsmentioning
confidence: 99%
“…A number of researchers find that the publics' perception of scientific consensus is a factor in the acceptance of science (Kahan et al 2011b;Lewandowsky et al 2012). These perceptions can affect whether societal action occurs to address climate-related issues and implement climate policy (Ding et al 2011;Kahan et al 2012;Rabinovich and Morton 2012). Recent public engagement with science and technology research (e.g.…”
Section: Conveying Scientific Information and Counsel To Decision Makersmentioning
confidence: 99%